Analisis Penetapan Prioritas Program Upaya Kesehatan Dasar (Puskesmas) pada Tingkat Pemerintah Daerah (Studi Eksploratif di Kota Bogor Tahun 2013) - Riastuti Kusuma Wardani (Jurnal Kebijakan Kesehatan Indonesia, 2014)
Background: A policy is a set of conceptual proposed action in order to achieve certain goals. Some health indicators in Bogor city government has increased but some has decreased or only slightly increased. Method: The study is qualitative methods, and the informants are District health office, Puskesmas, Regional Secretary of Bogor City and Regional Representative Council of Bogor City. We cross check the data by conducting document review and observation . Results: The main actors in setting program priorities are Bogor District health office using evidence-based policy . Support is dominated by an elite group of executive government which is the City Health Office . The elite in legislative also has major effect in the form of budget determination . Overview of the process reveals that any identified problem and issues of the health center depends on the areas of concern. The process of prioritization of primary health care programs in the health center in the city of Bogor using the top-down approach. Furthermore, the Bogor district health office is also coordinating and disseminate at the level of higher government organizers. Prioritization output of primary health care programs in health centers vary in accordance with their respective problems working areas. The program remains in accordance with the basic policy of mandatory basic health centers to run the affairs of primary health care . Conclusions: human resources, support and demand is the necessary input to the priority-setting process, howoever a larger portion of health office still affect prioritization. Bottom- up approach needs to be done on the basis of the data. Kebijakan adalah serangkaian konsep tindakan yang diusulkan dalam rangka mencapai tujuan tertentu. Beberapa indikator pembangunan kesehatan pemerintah daerah Kota Bogor mengalami peningkatan namun ada pula yang mengalami penurunan atau meningkat tetapi tidak signifikan. Metode: metode kualitatif dengan Informan ; Dinkes Kota, Puskesmas, Sekda Kota Bogor, DPRD Kota Bogor. Cross cek data dengan melakukan telaah dokumen dan observasi. Hasil: Input;aktor utama dalam penetapan prioritas program adalah Dinas Kesehatan Kota Bogor dengan evidence base policy. Dukungan didominasi oleh kelompok elit eksekutif pemerintah adalah Dinas Kesehatan Kota. Kelompok elit legislative juga memberikan pengaruh, dalam bentuk penetapan anggaran. Gambaran proses : Identifikasi masalah dan isu tergantung pada permasalahan Puskesmas. Proses penetapan prioritas program pelayanan kesehatan dasar pada Puskesmas di Kota Bogor menggunakan metode top down. Selanjutnya dinas pula yang melakukan koordinasi dan sosialisasi pada level penyelenggara pemerintahan yang lebih tinggi. Output penetapan prioritas program pelayanan kesehatan dasar pada Puskesmas berbeda-beda sesuai dengan permasalahan masing-masing wilayah kerjanya. Program tetap sesuai dengan kebijakan dasar Puskesmas menjalankan urusan wajibnya primary health care. Kesimpulan: SDM, dukungan dan tuntutan merupakan masukan bagi proses penetapan prioritas dengan porsi Dinkes lebih besar mempengaruhi penetapan prioritas. Pendekatan bottom up perlu dilakukan dengan berdasar pada data.